2021
DOI: 10.1371/journal.pone.0248982
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous digital technologies and spatial structure; an update

Abstract: This paper examines the impact of widespread adoption of information and communication technologies (ICT) on urban structure worldwide. Has it offset agglomeration benefits and led to more dispersed spatial structures, or has it strengthened urban externalities and thus resulted in more concentrated spatial structures? Theoretical and empirical studies on this question have produced contradictory findings. The present study recognizes that assumptions made earlier about the evolution of technological capabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 66 publications
0
10
2
Order By: Relevance
“…Our finding is different from the decentralization effect found by Ioannides et al (2008), Tranos and Ioannides (2015, 2020) and from the concentration effect found by Tranos and Ioannides (2021). The reason for this could be attributed to the difference between their sample countries and ours in the development phases of the internet.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our finding is different from the decentralization effect found by Ioannides et al (2008), Tranos and Ioannides (2015, 2020) and from the concentration effect found by Tranos and Ioannides (2021). The reason for this could be attributed to the difference between their sample countries and ours in the development phases of the internet.…”
Section: Discussioncontrasting
confidence: 99%
“…At the inflection point, the fixed broadband penetration rate is 18%, and the internet user rate is 45%, which is calculated based on 2.5 users per household. The percentage of internet users is less than 45% in almost all sample countries of Ioannides et al (2008) and in most sample countries of Tranos and Ioannides (2015, 2020), while that in most sample countries of Tranos and Ioannides (2021) is more than 50%. Almost all of sample countries used by Ioannides et al (2008), Tranos and Ioannides (2015, 2020) are on the left side of the inflection point in our study, and most sample countries used by Tranos and Ioannides (2021) are on the right side of the inflection point in our study.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations